A Discrepancy Model of End-User Computing Involvement - Doll, William J.; Torkzadeh, Gholamreza (Management Science, 1989)
Within the context of traditional data processing, the MIS literature has devoted considerable attention to the relationship between user involvement and MIS success: unfortunately, this research has produced conflicting results. After reviewing these results, Ives and Olson provide a framework for research on user involvement. Although their framework uses cognitive and motivational psychological mechanisms to explain the linkage between user involvement and MIS success, the contingency variables they identify do not pertain to individual differences between users. Thus, the framework has limitations that reduce its usefulness for explaining conflicting research findings, and its applicability to the end-user computing environment. End-user computing is an emerging phenomenon characterized by substantial differences between individuals in skill and motivation. The unique aspects of this dynamic end-user environment are identified here and an end-user involvement construct is described. Next, after reviewing the participative decision making literature, a model of end-user involvement based upon Alutto and Belasco's discrepancy concept of participation is presented. Focusing on individual differences, this model hypothesizes a contingency relationship between perceived involvement, desired involvement, and end-user satisfaction. Three intervening psychological mechanisms described by Locke and Schweiger (value attainment as well as cognitive and motivational) are used to provide a theoretical rationale for the linkage between involvement and end-user satisfaction. The model is empirically examined using a sample of 618 respondents from 44 firms. The results tend to support the contingency hypotheses. The usefulness of this model for reconciling conflicting research findings in the user involvement literature is discussed, and suggestions for further research are described.